2022
DOI: 10.26434/chemrxiv-2022-ldmbm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metal Complexes as Antifungals? – From a Crowd-Sourced Compound Library to First In Vivo Experiments

Abstract: There are currently fewer than ten antifungal drugs in clinical development, but new fungal strains, which are resistant to most current antifungals are spreading rapidly across the world. To prevent a second resistance crisis, new classes of antifungal drugs are urgently needed. Metal complexes have proven to be promising candidates for novel antibiotics, but so far, few compounds have been explored for their potential application as antifungal agents. In this work we report the evaluation of 1039 metal-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…90,91 At the same time, in order to avoid the development of resistance by the fungi, the recent research focus has been shifted to the investigation of biological activity of new classes of potential fungicides with novel modes of action, namely metallacomplex-based drugs. 92 Among these results, only three publications concern fungicidal activity of Mn-based complexes. 93−95 However, the focus of those experiments was strictly on human fungal infections, i.e.…”
Section: ■ Introductionmentioning
confidence: 99%
“…90,91 At the same time, in order to avoid the development of resistance by the fungi, the recent research focus has been shifted to the investigation of biological activity of new classes of potential fungicides with novel modes of action, namely metallacomplex-based drugs. 92 Among these results, only three publications concern fungicidal activity of Mn-based complexes. 93−95 However, the focus of those experiments was strictly on human fungal infections, i.e.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[8][9][10][11] The recent progress in this field has been highlighted in several review articles. [12,13] We have recently shown that metal complexes have superior hit-rates against critical bacteria [14] and fungi [15] in vitro compared to purely organic molecules. We could show that metal complexes did not possess higher rates of cytotoxicity or haemolysis against human cells compared to their organic counterparts.…”
Section: Introductionmentioning
confidence: 99%